HUBUNGAN ANTARA VOLUME CAVUM ORIS DENGAN FREKUENSI GELOMBANG SUARA PENGUCAPAN VOKAL (/i/, /u/), LINGUODENTAL (/t/, /d/), BIDENTAL (/s/) PADA MALOKLUSI ANGLE KLAS I BERJEJAL RINGAN (Kajian pada Anak Perempuan Usia 12-13 Tahun) - , OLIVIA TRIFINA NGO, Drg. Rinaldi Budi Utomo, M.S., Sp. KGA(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Speech is a sound and verbal expression of language, consisting of vowel and consonant phonemes. Speech is strongly influenced by physical factors (vocal tract), especially the volume of cavum oris. The purpose of this study was to determine the correlation between cavum oris volume and the speech of vowel (/i/, /u/), linguodental consonant (/t/, /d/) and bidental consonant (/s/) on the case of Angle Class I malocclusion with mild crowding. Observational study with cross sectional approach was performed in 10 children aged 12-13 years. Volume of cavum oris measurements made by duplicating the oral cavity and speech frequency analysis assessed by recording the speech of vowel (/i/, /u/), linguodental consonant (/t/, /d/) and consonant bidental (/s/) in morpheme. Data were analyzed by Pearson Product Moment Correlation test. The results showed a significant correlation between the volume of cavum oris with speech frequency of vowels (/i/, /u/), linguodental consonant (/t/, /d/), bidental consonant (/s/) (p <0,05). Negative values on r-value indicate the correlation in the opposite direction. The greater value of the cavum oris volume, the smaller the value of the frequency phoneme speech. The contribution cavum orisâ volume with speech frequency of /t/ phoneme was Â± 82,3%, /d/ Â± 83%, /s/ Â± 83,7%, /i/ Â± 82,4%, and /u/ Â± 86,2% . The results concluded that cavum oris volume have correlation with speech frequency of vowel (/i/, /u/), linguodental consonant phonemes (/t/, /d/), bidental consonant (/s/) in Angle Class I malocclusion with mild crowding. The greater the cavum orisâ volume, the smaller the speech frequency of vowel phonemes (/i/, /u/), linguodental consonant (/t/, /d/), bidental consonant (/s/). The highest frequency is speech of vowel /i/.